Basic Concepts of Evaluation and Assessment of English Language Learning in the Merdeka Curriculum - Arif Bulan; Enung Nurhasanah; Rusdin (PT. Banjarese Pacific Indonesia, 2024)
English language education has become a major focus in the education curriculum in many countries, as well as in Indonesia. In the context of the Merdeka Curriculum, evaluation and assessment of English learning play a crucial role in determining the successful implementation of the Merdeka curriculum. This study aims to (1) explore the basic concepts of evaluating English learning in the Merdeka curriculum, (1) explore English learning assessment in the Merdeka Curriculum, (3) and explore the challenges in evaluating and assessing English learning in the Merdeka curriculum. This research uses a literature review research method in which secondary sources are obtained from books and journals in supporting the study and findings. The results of this study First, the basic concepts of evaluating English learning in the independent curriculum include formative, summative and authentic assessment. Second, the assessment of the independent curriculum English language learning includes listening, reading, viewing, speaking and writing. Meanwhile, the challenges of evaluating and assessing English learning in the independent curriculum include the development of assessment instruments that are in accordance with the principles of the independent curriculum, the integration of continuous formative assessment in the independent curriculum, and aspects of inclusiveness in English learning.